Association of Sjögren's syndrome with myotonic dystrophy type 1. Issue 8 (28th August 2019) - Kitsis, Elizabeth A; Napier, Fabreena; Juthani, Viral; Geyer, Howard L
Abstract : A 47-year-old woman presented with sicca symptoms, polyarthralgias, polymyalgias and dysphagia. She was found to have positive antinuclear, anti-SSA-Ro and anti-SSB-La antibodies. Slit lamp exam confirmed the presence of keratoconjunctivitis sicca, and the patient was diagnosed with Sjögren's syndrome. Three years later, she was referred for evaluation of gait instability associated with recent falls. On physical examination, the patient was found to have bilateral ptosis, percussion myotonia, distal upper and lower extremity weakness, and a steppage gait. Electromyography demonstrated electrical myotonia. Genetic testing revealed expanded CTG repeats (733 and 533) in the myotonic dystrophy type 1 (DM1) protein kinase gene, confirming the diagnosis of DM1. Dysphagia, pain and eye discomfort may occur in both Sjögren's syndrome and DM1, and in this case, may have delayed the diagnosis of muscular dystrophy.